1984
DOI: 10.3133/ofr84867
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ground-water contamination by coal-tar derivatives, St. Louis Park area, Minnesota

Abstract: Operation of a coal-tar distillation and wood-preserving facility in St. Louis Park, Minnesota, during 1918-72 contaminated ground water with coal-tar derivatives and inorganic chemicals. Coal-tar derivatives entered the groundwater system through three major paths: (1) Spills and drippings that percolated to the water table, (2) surface runoff and plant process water that was discharged to wetlands south of the former plant site, and (3) movement of coal tar directly into bedrock aquifers through a multiaquif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…(See figure 48.) Coal-tar derivatives migrated northward in the Prairie du Chien-Jordan aquifer because of local reversals in the regional gradient caused by groundwater withdrawals and the flow of water into the aquifer from other aquifers through wells that tap several aquifers (multiaquifer wells) (Hult, 1984). Aided by computer simulations of ground-water flow (Stark and Hult, 1985a,b), Federal, State, and local agency personnel and representatives of the former plant have designed a system to control hydraulic gradients and, thereby, the direction of contaminant transport in the Prairie du Chien-Jordan aquifer and to treat and use contaminated water from the wells.…”
Section: Discussionmentioning
confidence: 99%
“…(See figure 48.) Coal-tar derivatives migrated northward in the Prairie du Chien-Jordan aquifer because of local reversals in the regional gradient caused by groundwater withdrawals and the flow of water into the aquifer from other aquifers through wells that tap several aquifers (multiaquifer wells) (Hult, 1984). Aided by computer simulations of ground-water flow (Stark and Hult, 1985a,b), Federal, State, and local agency personnel and representatives of the former plant have designed a system to control hydraulic gradients and, thereby, the direction of contaminant transport in the Prairie du Chien-Jordan aquifer and to treat and use contaminated water from the wells.…”
Section: Discussionmentioning
confidence: 99%
“…Hult and Schoenberg (1984) present an overview of the problem. Hult (1984) and Stark and Hult (1985) discuss contamination of the Prairie du Chien-Jordan aquifer and document the construction and calibration of a three-dimensional ground-water-flow model used to evaluate pumping strategies to control ground-water movement in the Prairie du Chien-Jordan aquifer. This report evaluates various pumping strategies to control ground-water movement in the St. Peter aquifer.…”
mentioning
confidence: 99%
“…Ground-water flow in the St. Peteriaquife:: moves in a general west to east direction near the plant site (Hult, 1984 ment into the St. Peter aquifer has been influenced by flow in a multiaquifer well located on the plant site, by othei: nearby multiaquifer wells, by stresses from production wells and by downward grounl-water flow in bedrock valleys. Hult (1984) and Ehrlich and others (1982) presented data that showed that the concentrations of several inorganic constituents, resulting from activities at (Trace of section shown in Figure 4) (Hydrogeology from Hult, 1984, p. 19) the plant site decreased downgradient in the glacial-drift aquifers. The data also showed that the concentrations of the constituents were elevated near a bedrock valley.…”
mentioning
confidence: 99%